The Effect of E-Service Quality and Brand Image on E-Loyalty through Brand Trust and E-Satisfaction as Intervening Variables - Feliciana Regina Putri; Farida Indriani (Budapest International Research and Critics University, 2022)
This study aims to examine the effect of e-service quality and brand image on e-loyalty traveloka customers through brand trust and e-satisfaction as an intervening variable. Sampling was used using purposive sampling technique, total samples used as many as 276 respondents who had been a consumer of Traveloka and had made a purchase in Traveloka for a minimum of 2 times. The data analysis technique used in this study was to use SEM (Structural Equation Model) analysis with the AMOS program, and data collection techniques used a questionnaire. The results showed that E-Service Quality and Brand Image had a positive effect on the customer e-satisfaction. Brand Trust and e-satisfaction have a positive effect on e-loyalty and brand image positively influence the brand trust